The Subaru Coronagraphic Extreme Adaptive Optics System: Enabling High-Contrast Imaging on Solar-System Scales. (4th January 2016) - Jovanovic, N.; Martinache, F.; Guyon, O.; Clergeon, C.; Singh, G.; Kudo, T.; Garrel, V.; Newman, K.; Doughty, D.; Lozi, J.; Males, J.; Minowa, Y.; et al.
Abstract: The Subaru Coronagraphic Extreme Adaptive Optics (SCExAO) instrument is a multipurpose high-contrast imaging platform designed for the discovery and detailed characterization of exoplanetary systems and serves as a testbed for high-contrast imaging technologies for ELTs. It is a multiband instrument which makes use of light from 600 to 2500 nm, allowing for coronagraphic direct exoplanet imaging of the inner 3λ/ D from the stellar host. Wavefront sensing and control are key to the operation of SCExAO. A partial correction of low-order modes is provided by Subaru's facility adaptive optics system with the final correction, including high-order modes, implemented downstream by a combination of a visible pyramid wavefront sensor and a 2000-element deformable mirror. The well-corrected NIR (y-K bands) wavefronts can then be injected into any of the available coronagraphs, including but not limited to the phase-induced amplitude apodization and the vector vortex coronagraphs, both of which offer an inner working angle as low as 1λ/ D . Noncommon path, low-order aberrations are sensed with a coronagraphic low-order wavefront sensor in the infrared (IR). Low noise, high frame rate NIR detectors allow for active speckle nulling and coherent differential imaging, while the HAWAII 2RG detector in the HiCIAO imager and/or the CHARIS integral field spectrograph (from mid-2016) can take deeper exposures and/or perform angular, spectral, and polarimetric differential imaging. Science in the visible is provided by two interferometric modules: VAMPIRES and FIRST, which enable subdiffraction limited imaging in the visible region with polarimetric and spectroscopic capabilities respectively. We describe the instrument in detail and present preliminary results both on-sky and in the laboratory.